Pre-Course Inquiries - Ika Fitriani; Akhmad Zainur Ridla; Rizki Febri Andika Hudori (Pioneer: Journal of Language and Literature, 2023)
Need analysis is a pivotal process prior to starting any courses in order to get initial classroom mapping about students’ needs and expectations. This current study aims to describe the result of need analysis conducted prior to the course of Bahasa Inggris for nursing students. The method employed is descriptive quantitative using data that were collected through questionnaires distributed to the students who are taking Bahasa Inggris course in the odd semester 2022/2023. The results show several points, such as the students belonged to the beginner to intermediate level of English users who merely used English in the classroom contexts. The most challenging language skill is speaking, yet they have had learning awareness to acquire all the language skills in the targeted language. The students also propose some criteria of good teaching materials, learning activities, as well as assessment forms. Finally, the result of this current study can be one of the considerations or the basis for future learning designers, course facilitators, and institutions to design the course which meets the students’ needs.